Cosmetology: An Ayurvedic Vision - Gupta, Preeti; Verma, Jwala; Singh, Chandan; Purvia, Rajendra Prasad; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2022)
Background- Ayurveda is an ancient science of indigenous medicine, which is special in respect that, it is not only a medical science but is an art of living in human beings. There is a great demand of Ayurveda in the field of cosmetology due to its unique concept about beauty and its effective, cheaper and long-lasting beauty therapy without any side effect. Some medicinal plants like- Haridra, Manjistha, Sariva, Chandana, Amalaki, Ghritkumari, Babul, Lavanga, Shikakai, Ritha, Bhringaraj etc. have been prescribed for beautification of skin, hair, etc. Review methods- The studies done in previous years were found using Medline, Pubmed, Google scholar and by manual search. The searches conducted for determining the role of Ayurveda in cosmetology were included in this study. Results- It has been tried to keenly understand the role of Ayurveda in cosmetology from various aspects. The present review deals with the advantages of Ayurveda in Cosmetology, ayurvedic medicines & medicinal plants as cosmetics. Conclusion- After reviewing the classical texts and several articles, it has been concluded that Ayurvedic beauty concepts and products have bright future in cosmetology. The increased demand for the natural product has created new avenues in cosmeceutical market.